The impact of parasitoids on diamondback moth in Europe: a life table approach. Issue 6 (16th December 2021) - Haye, Tim; Dancau, Tina; Bennett, Andrew M. R.; Mason, Peter G.
Abstract: Diamondback moth, Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae), was first recorded in North America from Europe about 150 years ago and can be a significant pest of canola in Western Canada. Because parasitism of P. xylostella in Canada is generally low, the introduction of one or more additional exotic parasitoids from Europe is being considered to increase the suppression of P. xylostella populations. Life table studies to determine the impact of parasitoids on diamondback moth populations in Europe were conducted in northwestern Switzerland in 2014–2016. Net reproductive rates were found to be less than one in seven out of eight life tables, suggesting that P. xylostella populations in Switzerland are mostly driven by immigration and recolonisation. In total, seven primary parasitoid species and one hyperparasitoid were associated with diamondback moth. Pupal parasitism by D. collaris reached up to 30%, but because generational mortality was mainly driven by abiotic mortality factors and predation of larvae, the overall contribution of pupal parasitism was low (< 6%). In regions of Canada, where P. xylostella may have increasing populations and low larval mortality, the addition of D. collaris may be a promising approach. Life table studies across Canada are necessary to determine the need for such intervention.